Numerical simulations of collisional disruption of rotating gravitational aggregates: Dependence on material properties. (March 2015) - Ballouz, R.-L.; Richardson, D.C.; Michel, P.; Schwartz, S.R.; Yu, Y.
Abstract: Our knowledge of the strengths of small bodies in the Solar System is limited by our poor understanding of their internal structures, and this, in turn, clouds our understanding of the formation and evolution of these bodies. Observations of the rotational states of asteroids whose diameters are larger than a few hundreds of meters have revealed that they are dominated by gravity and that most are unlikely to be monoliths; however, there is a wide range of plausible internal structures. Numerical and analytical studies of shape and spin limits of gravitational aggregates and their collisional evolution show a strong dependence on shear strength. In order to study this effect, we carry out a systematic exploration of the dependence of collision outcomes on dissipation and friction parameters of the material components making up the bodies. We simulate the catastrophic disruption (leading to the largest remnant retaining 50% of the original mass) of km-size asteroids modeled as gravitational aggregates usingpkdgrav, a cosmology N -body code adapted to collisional problems and recently enhanced with a new soft-sphere collision algorithm that includes more realistic contact forces. We find that for a range of three different materials, higher friction and dissipation values increase the catastrophic disruption threshold by about half a magnitude. Furthermore, we find that pre-impact rotation systematically increases mass loss on average, regardless of the target׳s internal configuration. Our results have important implications for the efficiency of planet formation via planetesimal growth, and also more generally to estimate the impact energy threshold for catastrophic disruption, as this generally has only been evaluated for non-spinning bodies without detailed consideration of material properties. Abstract : Highlights: We model the catastrophic disruption of km-size planetesimals. We examine the dependence of mass loss on shear strength and pre-impact rotation. We vary shear strength by using three experimentally determined material properties. Increasing shear strength will increase the catastrophic disruption threshold ( Q RD ⁎ ). For different materials, rotation causes equivalent fractional changes in Q RD ⁎ .